2022
DOI: 10.1109/tem.2021.3084884
|View full text |Cite
|
Sign up to set email alerts
|

From Acquaintances to Partners in Innovation: An Analysis of 20 Years of Design Thinking's Contribution to New Product Development

Abstract: Scholars have suggested that design thinking (DT) should form an integral part of the new product development (NPD) process. However, the contribution of DT to NPD over the past years is yet to be synthesized. In this article, we develop a conceptual framework categorizing how DT contributes to NPD, and present a map to visualize how research in the area of DT in NPD has evolved over the past 20 years. A systematic analysis of 89 journal papers published between 2000 and 2020 helped to generate a conceptual fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…Another view, presented by Cooper et al, is that design thinking is seen as a reflective practicethat is, regarding mindset/mindset (Roth, Globocnik, Rau, & Neyer, 2020). Whereas in recent research it was found that design thinking is a tool to help a company create value and vision (de Paula et al, 2021). From this point of view, it means that design thinking helps organizations to find and apply the best user-centered mindset to find hidden needs that have not been touched as well as the creation of new business models.…”
Section: Understanding Of Design Thinkingmentioning
confidence: 99%
See 3 more Smart Citations
“…Another view, presented by Cooper et al, is that design thinking is seen as a reflective practicethat is, regarding mindset/mindset (Roth, Globocnik, Rau, & Neyer, 2020). Whereas in recent research it was found that design thinking is a tool to help a company create value and vision (de Paula et al, 2021). From this point of view, it means that design thinking helps organizations to find and apply the best user-centered mindset to find hidden needs that have not been touched as well as the creation of new business models.…”
Section: Understanding Of Design Thinkingmentioning
confidence: 99%
“…Discourses that support the use of design thinking as an organizational resource in recent years have gained a lot of traction, especially in the fields of design and management. The possibility that design thinking can do is expand the ability to innovate in organizations because that ability can encourage collaboration and the development of a user-centered mindset (de Paula et al, 2021). For the sake of creating innovation and economic growth, support is needed to investigate how design thinking can be used as an organizational resource to improve all product development processes (Magistretti et al, 2021;Neri, Cagno, Lepri, & Trianni, 2021).…”
Section: The Latest Of Design Thinkingmentioning
confidence: 99%
See 2 more Smart Citations
“…Our review complements previous reviews by a more holistic approach. Previous reviews focused on the characteristics of DT (Micheli et al ., 2019), on DT and organizational culture (Elsbach and Stigliani, 2018), and recently on DT and new product development (De Paula et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%